2018
DOI: 10.1159/000487434
|View full text |Cite
|
Sign up to set email alerts
|

Low Necroptosis Process Predicts Poor Treatment Outcome of Human Papillomavirus Positive Cervical Cancers by Decreasing Tumor-Associated Macrophages M1 Polarization

Abstract: Background/Aim: The aim of this study was to assess the functions of the necroptosis process on the prognosis of high-risk human papillomavirus (HR-HPV)-related cervical cancer. Methods: PCR and western blotting were used to demonstrate the expression of the necroptosis marker, mixed lineage kinase domain-like protein (MLKL), in whole blood and peripheral blood mononuclears (PBMCs) of 89 cervical cancer patients and 15 healthy volunteers. Necroptosis levels and M1 polarization were determined in tumor co-cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Additionally, RIPK3 mRNA is decreased in human colorectal cancer (CRC) tissues compared to healthy colon controls [75], and loss of RIPK3 is associated with tumor progression in CRC [76]. Conversely, increased expression of RIPK3 positively correlates with favorable outcomes in a variety of human tumors, including HPV + cervical cancer [77] and AML [78]. Consistent with the idea that RIPK3 expression promotes antitumor responses, the locus of the RIPK3 gene (chromosome 14q11.2) [79] is frequently mutated in several types of neoplasia, including nasopharyngeal carcinoma [80] and acute lymphoblastic leukemia [81], although it remains to be determined whether these mutations are specifically within the RIPK3 gene.…”
Section: Roles For Necroptosis During Oncogenesismentioning
confidence: 99%
“…Additionally, RIPK3 mRNA is decreased in human colorectal cancer (CRC) tissues compared to healthy colon controls [75], and loss of RIPK3 is associated with tumor progression in CRC [76]. Conversely, increased expression of RIPK3 positively correlates with favorable outcomes in a variety of human tumors, including HPV + cervical cancer [77] and AML [78]. Consistent with the idea that RIPK3 expression promotes antitumor responses, the locus of the RIPK3 gene (chromosome 14q11.2) [79] is frequently mutated in several types of neoplasia, including nasopharyngeal carcinoma [80] and acute lymphoblastic leukemia [81], although it remains to be determined whether these mutations are specifically within the RIPK3 gene.…”
Section: Roles For Necroptosis During Oncogenesismentioning
confidence: 99%
“…Decreased overall survival and disease-free survival [229] Ovarian cancer Decreased overall survival. [230] Pancreatic adenocarcinoma…”
Section: Low Expressionmentioning
confidence: 99%
“…It was further discovered that when treated with the supernatant of CC cell lines, M1-like macrophages developed an M2-like phenotype with increased CD163, TLR-3, -7, -9 and IL-10 [25,26]. Similarly, co-culture cervical cancer cells decrease the macrophage M1-like polarization partly through necroptosis downregulation [27]. However, these studies did not clarify which component of the supernatant was responsible for the M2-like induction.…”
Section: The Molecules Involved In Forming Tamsmentioning
confidence: 99%
“…These studies showed TAMs in CC have a M2-like phenotype because most infiltrating and pro-tumor macrophages were M2-like. M1-like macrophages existed in the CC tumor stroma with a declined expression of M1-like markers such as IL-6, TNF-α and iNOS and tendedto transfer to M2-like phenotype under the influence of tumor cells [27]. Other markers of M1-like were also used in CC research such as CD163- [25,89], CD163+ pSTAT1 [90], IL-12p40 [27], CD80+ [26], HLA-DR [26] and CXCL10 [35].…”
Section: Biomarkers Of Tamsmentioning
confidence: 99%
See 1 more Smart Citation